2020
DOI: 10.1007/s10439-020-02449-5
|View full text |Cite|
|
Sign up to set email alerts
|

An Integrated In Vitro–In Silico Approach for Silver Nanoparticle Dosimetry in Cell Cultures

Abstract: Potential human and environmental hazards resulting from the exposure of living organisms to silver nanoparticles (Ag NPs) have been the subject of intensive discussion in the last decade. Despite the growing use of Ag NPs in biomedical applications, a quantification of the toxic effects as a function of the total silver mass reaching cells (namely, target cell dose) is still needed. To provide a more accurate dose-response analysis, we propose a novel integrated approach combining well-established computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…In order to reduce the use of animal testing, humane experimental techniques have been employed to investigate biological and pathological effects as alternative forms of nanomaterial toxicity assessments. In this review, we introduce that in vitro cell-based models and in silico computational models are the most commonly used alternative testing tools to evaluate the safety and toxicity of chemical substances in the field of nanotechnology (Figure 1) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the use of animal testing, humane experimental techniques have been employed to investigate biological and pathological effects as alternative forms of nanomaterial toxicity assessments. In this review, we introduce that in vitro cell-based models and in silico computational models are the most commonly used alternative testing tools to evaluate the safety and toxicity of chemical substances in the field of nanotechnology (Figure 1) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the ability to aerosolize particles is a must for investigating the interactions between cells and inhaled particles, as is the ability to accurately dose the amount of material coming in contact with the cells. 217 As discussed in the section on exposure systems, there are commercial devices that meet such characteristics and are becoming standards for toxicology, including the testing of cigarette and tobacco products, since in these cases a high level of reproducibility is demanded. Moreover, the requirement for reproducibility reflects the favored use of commercial 3D cell models in several of the studies reported in the section on exposure systems and summarized in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…A proper definition of the cytotoxic “potential” of a specific NP would require correlating harmful effects to the cumulative amount of material effectively interacting with cells during the exposure test, or what we refer to as the “effective dose” [9], [10]. Cells in culture are known to be sensitive to NPs (and their dissolved ions) that are internalized or even in their immediate vicinity.…”
Section: Introductionmentioning
confidence: 99%